Pengaruh Kemiringan Lereng Terhadap Komposisi Fraksi Tanah Pada Berbagai Posisi Lereng - Siswanto, Shantosa Yudha; Solihin, M. Amir (Dept Ilmu Tanah & Sumberdaya Lahan Fakultas Pertanian Universitas Padjadjaran, 2023)
The research is carried out to see the impact of slope steepness differences with different slope positions on the composition of soil fractions in Cikeruh catchment. The fieldwork in this research is carried out based on physiographic appearance and is also known as the free physiographic survey method. Soil samples were taken at slopes 8-15%, 15-25%, and 25-40% with four replications. Thus, there were a total of 36 sample points. The result conclude that slope steepness gave a significant impact on soil fraction composition.